Does Mind Mapping Technique Improve Cohesion and Coherence in Composition Writing? An Experimental Study - Muhammad Naqeeb ul Khalil Shaheen, Nazir Haider Shah, Hajira Naqeeb (PJE, 2023)
The purpose of this study was to compare the effectiveness of teaching technique based on mind mapping to improve cohesion and coherence in tenth grade students' composition writing. The study used a pre-test and post-test control group design. Sixty (60) junior high school students (30 boys and 30 girls) from two schools were randomly selected.